Gene Effect Analysis for Grain Yield, Yield Components and Physiological Characters in Bread Wheat Under Water Limited Conditions of Bundelkhand Region - Saini, Manoj Kumar; Kumar, Vishnu; Supriya, Patel; Singh, Sultan; Singh, Krishna Kunwar; Chaturvedi, Sushil Kumar (International Journal of Bio-resource and Stress Management, 2023)
The present study was conducted during rabi, 2019-20 and 2020-21 with 08 bread wheat diverse parents and their 28 F1s (half diallel, excluding reciprocals) to study gene effects and heterosis for grain yield, yield attributes and physiological traits. Days to heading and days to maturity had general mean values of 89.8 days and 130.4 days, respectively. The parent GW 322 showed early heading in 88 days, while the genotype DBW 110 exhibited early maturity in 128 days. The hybrid NW 5054×PBW 723 (13.45 cm) had the highest spike length, followed by HD 3086×NW 5054 (13.40 cm) and PBW 723×NIAW 34 (13.25 cm). The grain yield per plant ranged from 17.37 g to 21.85 g in parents and 14.99 g to 23.41 g among hybrids. The cross HD 3086×K 1006 (23.41 g) and the parent HD 3086 (21.85 g) depicted the highest grain yield per plant. The parent NIAW 34 and the hybrid HD 3086×NIAW 34 showed the highest chlorophyll fluorescence. All three key physiological traits showed significant and positive associations with grain yield and harvest index. All the seventeen characters showed high GCA effects than SCA effects and indicated for preponderance of additive gene effects for yield, its components and physiological traits. An appraisal of GCA effects found that HD 3086 was a good general combiner for the majority of characters, while the crosses, HI 1544×NIAW 34, HI 1544×GW 322 and NW5054×PBW723 with significant SCA effects were found promising under water limited conditions of Bundelkhand region.